2010
DOI: 10.1111/j.1468-3083.2009.03533.x
|View full text |Cite
|
Sign up to set email alerts
|

Candida balanitis: risk factors

Abstract: This study highlights the impact of factors other than sexual behaviours upon the epidemiology of this infection. For both candida colonization and infection, age was an important risk factor. Diabetes mellitus was an independent risk factor for candida balanitis. More than ten colonies recovered from culture are associated with clinical signs and symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 26 publications
0
34
1
6
Order By: Relevance
“…9 Lisboa et al studied the risk factors for Candida balanitis in 478 men, and their frequency. They found that DM and age over 40 were two significant factors in 18% of their cases, versus other factors, such as same sex intercourse, and no circumcision, which were nonsignificant.…”
Section: Discussionmentioning
confidence: 99%
“…9 Lisboa et al studied the risk factors for Candida balanitis in 478 men, and their frequency. They found that DM and age over 40 were two significant factors in 18% of their cases, versus other factors, such as same sex intercourse, and no circumcision, which were nonsignificant.…”
Section: Discussionmentioning
confidence: 99%
“…Candida spp, se presenta aproximadamente en un tercio de las pacientes diagnosticadas con vulvovaginitis [5,9,[13][14][17][18][19][20][21][22][23][24][25][26]. Ocasionalmente se reportan casos de candidosis en el aparato genital masculino [3]; un estudio efectuado en 478 hombres demostró a Candida en el 26% como colonizante y en 18% como causante de balanitis [27].…”
Section: Vulvovaginitis Infecciosaunclassified
“…En algunos casos no es posible dilucidar algún factor, estableciéndose el diagnóstico de candidosis vulvovaginal idiopática. Es poco común el hallazgo de levaduras en el pene de hombres parejas de mujeres colonizadas por Candida [2][3][4]27].…”
Section: Etiología De Las Vulvovaginitis Por Candida (Vvc)unclassified
See 2 more Smart Citations